2017
DOI: 10.1371/journal.pone.0175182
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol abstinence and risk assessment for second esophageal cancer in Japanese men after mucosectomy for early esophageal cancer

Abstract: BackgroundAlcohol consumption combined with inactive aldehyde dehydrogenase-2 (ALDH2) and the presence of multiple esophageal Lugol-voiding lesions (LVLs; dysplasia) are strong predictors for multiple development of esophageal squamous cell carcinoma (ESCC) in East Asians. We invented a health risk appraisal (HRA) model for predicting the risk of ESCC based on drinking, smoking, dietary habits, and alcohol flushing, i.e., past or present facial flushing after drinking a glass of beer, a surrogate marker for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 37 publications
3
19
2
Order By: Relevance
“…Alcohol flushing response is associated with an inherited deficiency in the enzyme aldehyde dehydrogenase 2 (ALDH2), leading to accumulation of acetylaldehyde. 28 Only a few studies have investigated the influence of TNM stage of HNSCC on synchronous ESCN, and their results were inconsistent. 26 A review article also concluded heavy drinkers with alcohol flushing response as a high-risk subpopulation likely to develop multiple upper aerodigestive tract cancers for whom they recommended endoscopic surveillance for ESCN.…”
Section: Cancer Epidemiologymentioning
confidence: 64%
See 1 more Smart Citation
“…Alcohol flushing response is associated with an inherited deficiency in the enzyme aldehyde dehydrogenase 2 (ALDH2), leading to accumulation of acetylaldehyde. 28 Only a few studies have investigated the influence of TNM stage of HNSCC on synchronous ESCN, and their results were inconsistent. 26 A review article also concluded heavy drinkers with alcohol flushing response as a high-risk subpopulation likely to develop multiple upper aerodigestive tract cancers for whom they recommended endoscopic surveillance for ESCN.…”
Section: Cancer Epidemiologymentioning
confidence: 64%
“…In Japan, a risk appraisal model incorporating factors including alcohol flush response can predict the risk of developing metachronous esophageal SCC among patients received mucosectomy of the early esophageal SCC. 28 Only a few studies have investigated the influence of TNM stage of HNSCC on synchronous ESCN, and their results were inconsistent. [11][12][13]16 We found only distant metastasis from HNSCC to be an independent risk factor for synchronous high-grade dysplasia/SCC in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Yokoyama et al . conducted a post hoc analysis of 278 men from the above‐mentioned prospective cohort study.…”
Section: Part 1: Esophageal Squamous Cell Carcinomamentioning
confidence: 99%
“…The metachronous cancer rates are considerably high and surveillance endoscopy should be performed carefully. Abstinence from alcohol is also important to prevent recurrence [ 42 , 43 ].…”
Section: Cumulative Metachronous Cancer Rate After Esophageal Esdmentioning
confidence: 99%